Prevalence of knowledge, attitude and practice on pesticides safety among oil palm pesticide handlers in Johor - Mior Iskandar Shah, Siti Nazhatul Marina (2017)
Awareness on possible risk factor in pesticides, by the change of attitude such as applying correct technique during spraying and change of behaviour can increase the safety and performance of workers. However in Malaysia, there are limited studies that cover or highlighted deeply the knowledge, attitude and practice of the workers.Moderate or low level of knowledge could put farm workers at risk when contact is made with pesticide residue on plants, soil, and dust particles after spraying.The objective of this study is to assess the level of knowledge, attitudes and practices of pesticide usage among oil palm plantation workers in Johor and to identify the relationship between knowledge, attitude and pesticides practice of the workers. This study is quantitative in nature and involved 132 respondents which represents 90% of the population of oil palm workers in Johor. Bivariate correlation indicates that there were significant relationships between knowledge and practice. It is found that only Knowledge-Practice (P-K) is found to be highly significant (r < 0.05) . This shows that higher knowledge will result to safer practice. There is no relationship between knowledge and attitude and between attitude and practice. Majority of respondents shows moderate level of knowledge (72%) and attitude (79%) but safer level of practice (85%). This study shows that the knowledge of these workers need to be strengthen in agricultural community of Johor in order to reduce number of accidents, current statistics and for any future incidents.